Structure and composition of mangrove vegetation in the coastal area of Mandalika International Street Circuit, Central Lombok, Indonesia - EDI MUHAMAD JAYADI; FIRMAN ALI RAHMAN; MUHAMMAD SHOHIBUL IHSAN; LENY FITRIAH; DWI AGUSTINI (Society for Indonesian Biodiversity, 2024)
Abstract. Jayadi EM, Rahman FA, Ihsan MS, Fitriah L, Agustini D. 2024. Structure and composition of mangrove vegetation in the coastal area of Mandalika International Street Circuit, Central Lombok, Indonesia. Biodiversitas 25: 2719-2728. Mangrove is one of the coastal vegetation that has an ecological role as a buffer for essential areas such as the Mandalika International Street Circuit Special Economic Zone located around the coastal area of Central Lombok District, West Nusa Tenggara, Indonesia. This research, conducted with a rigorous methodology, aims to determine the current condition of the diversity of mangrove vegetation and their vegetation structure as a buffer ecosystem in the Mandalika International Street Circuit area, West Nusa Tenggara. The study utilized the quadrant transect method, a widely accepted approach, with plots measuring 2×2 m2 (seedling strata), 5×5 m2 (sapling strata), 10×10 m2 (pole strata), and 20×20 m2 (tree strata). The total number of observation plots was 49 measuring plots in a total area of the mangrove ecosystem of 38.68 ha. The research results showed that four families and five genera were found consisting of 11 species of mangroves: Avicennia alba Blume, Avicennia lanata Ridl., Avicennia marina (Forssk.) Vierh., Ceriops tagal (Perr.) C.B.Rob., Rhizophora apiculata Blume, Rhizophora mucronata Lam., Rhizophora stylosa Griffith, Scyphiphora hydrophyllaceae C.F.Gaertn., Sonneratia alba Sm., Sonneratia caseolaris (L.) Engl., and Sonneratia ovata Backer. Rhizophora apiculata is the species with the highest density in the strata of seedlings (261 individuals/ha), saplings (312 individuals/ha), poles (444 individuals/ha), and trees (160 individuals/ha); this condition is in line with the importance value index R. apiculata with the highest values in seedlings (105.21%), saplings (89.14%), poles (129.61%), and trees (119.60%). Shannon-Wiener diversity index in the mangrove ecosystem in the Mandalika International Street Circuit is in the quite good category with an even diversity value with an H' value of no less than 1 (1.425).